Institutional Quality, Knightian Uncertainty, and Insurability : A Cross-Country Analysis - Erbas, S. (IMF Working Papers; Working Paper ;, 2006)
Knightian uncertainty (ambiguity) implies presence of uninsurable risks. Institutional quality may be a good indicator of Knightian uncertainty. This paper correlates non-life insurance penetration in 70 countries with income level, financial sector depth, country risk, a measure of cost of insurance, and the World Bank governance indexes. We find that institutional quality-transparency-uncertainty nexus is the dominant determinant of insurability across countries, surpassing the explanatory power of income level. Institutional quality, as it reflects on the level of uncertainty, is the deeper determinant of insurability. Insurability is lower when governance is weaker.